Penerapan Koefisien Aliran untuk Mendukung Budidaya Tanaman Bernilai Ekonomi Tinggi (Studi Kasus: Kwanyar Bangkalan, Indonesia) - Widya Utama; Anicetus Wihardjaka; Nourma Al Viandari; Dwa Desa Warnana; Wien Lestari; Eki Komara; Sherly Ardhya Garini; Rista Fitri Indriani; Dhea Pratama Novian Putra; Annisa R. Varhana (Postgraduate, University of Mataram, 2023)
The initial study that we carried out regarding the Kwanyar sub-district area, Bangkalan, East Java, shows the need to optimize land productivity and analyze the potential for farming to build the welfare of the people of the Kwanyar subdistrict. Preliminary spatial data analysis related to the topography as a result of Digital Elevation Model (DEM) data processing shows that: the Kwanyar sub-district is dominated by flat slopes (0-8Â°) compared to the northern region of the Kwanyar sub-district, while runoff water analysis shows a low flow coefficient (0- 0.25) which means that most of the Kwanyar area has low absorption capacity and a high potential for stagnant water. In addition, the Kwanyar region has a Regosol soil type. Regosol soil has a coarse texture and low organic matter, which makes it unable to properly hold water and minerals for plants, so it tends to be infertile. The initial study then became the basis for this research.